2014
DOI: 10.1007/jhep08(2014)035
|View full text |Cite
|
Sign up to set email alerts
|

NNLO QCD subtraction for top-antitop production in the q q ¯ $$ q\overline{q} $$ channel

Abstract: We present the computation of the double real and real-virtual contributions to top-antitop pair production in the quark-antiquark channel at leading colour. The qq → ttg amplitudes contributing to the real-virtual part are computed with OpenLoops, and their numerical stability in the soft and collinear regions is found to be sufficiently high to perform a realistic NNLO calculation in double precision. The subtraction terms required at real-real and real-virtual levels are constructed within the antenna subtr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 78 publications
1
54
0
Order By: Relevance
“…This has been possible thanks to the development of subtraction schemes [62][63][64][65][66][67][68][69][70], slicing methods [60,61,71] and the calculation of several two-to-two virtual amplitudes [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. As far as top-quark pair production is concerned, besides our own calculation [10,92] only partial results are known at the differential level [93,94]; there is also progress at the level of total crosssection [95] obtained with slicing methods.…”
Section: Jhep05(2016)034mentioning
confidence: 99%
“…This has been possible thanks to the development of subtraction schemes [62][63][64][65][66][67][68][69][70], slicing methods [60,61,71] and the calculation of several two-to-two virtual amplitudes [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91]. As far as top-quark pair production is concerned, besides our own calculation [10,92] only partial results are known at the differential level [93,94]; there is also progress at the level of total crosssection [95] obtained with slicing methods.…”
Section: Jhep05(2016)034mentioning
confidence: 99%
“…In [6], where we studied the leading colour contributions to top-pair production in the qq channel, it was shown that the subtraction terms constructed at the real-real and real-virtual level approximate the corresponding matrix-elements in all their infrared limits. Furthermore, an explicit and analytic pole cancellation occurs at the real-virtual level between explicit infrared poles of the one-loop matrix-elements and those from integrated double real subtraction terms.…”
Section: Pos(ll2014)002mentioning
confidence: 99%
“…The integration of the (subtracted) one-loop contributions over the soft and collinear regions of phase space can lead to serious numerical instabilities. This issue has been addressed in [6]. It was shown that using the…”
Section: Pos(ll2014)002mentioning
confidence: 99%
See 2 more Smart Citations